Statistical Modeling for Indian GDP, Export and Import - Rajarathinam A.; Manikandan B. (An Overview on Business, Management and Economics Research Vol. 3, 2023)
This chapter investigates the relationship between GDP, exports, and imports. The main objective of this chapter is to analyze the dynamic links between India’s GDP, exports, and imports using data collected every year between 1950 and 2014. Gross domestic product (GDP) is a monetary measure of the market value of all the final goods and services produced in a specific time period by a country or countries. GDP is most often used by the government of a single country to measure its economic health. Due to its complex and subjective nature, this measure is often revised before being considered a reliable indicator. The Jarque-Bera test (used to check for normality), the Augmented Dickey-Fuller unit root test, the Phillips-Perron unit root test, the KPSS test (used to check for stationarity), and the Johansen Co-integration test (used to check for the number of con-integrating relationships among the underlying variables) are among the various econometrics tools. Vector Error Correction Model (to ascertain the variables’ long-term relationships with one another) Both the Granger causation test and the Wald test have been used to determine the direction of causation. The stationarity test findings showed that the three variables under consideration have unit roots at level I(0), but that they become stationary at level I(1) after being transformed into the first difference. The trace and Max-eigenvalue test statistics of Johansen’s Co-integration test indicated the existence of two co-integrating equations and exhibited a long-run equilibrium relationship between the study variables. In the Vector Error Correction Model, C(1) is the coefficient of the error correction (co-integration) model, which is negative and significant, indicating a long-run causality running from import and export to GDP. The Wald test indicates that there are short-run causalities running from export to GDP and no short-run causality running from import to GDP. The Granger Causality test reveals that bidirectional causality exists between export and GDP and unidirectional causality between import and GDP. The residuals due to the Vector Error Correction Model are independent (no autocorrelation) and normally distributed. Also, the VECM model is free from Heteroskedasticity.